Earnings management, board of directors, and earnings persistence: Indonesian evidence - Wing Wahyu Winarno; Krismiaji Krismiaji; Handayani Handayani; Maria Purwantini (Jurnal Akuntansi dan Auditing Indonesia, 2022)
This research investigates the impacts of earnings management, both accrual earnings management (AEM) and real earnings management (REM), as well as Board of Directors (BOD) on earnings persistence. Accrual earnings management was measured using Modified Jone's Model, and real earnings management was assessed by three measures: abnormal cash flow, abnormal production expenditure, and abnormal discretionary expenditure. In addition, Board of Directors was measured using BOD size and BOD independence. Earnings persistence was measured based on the current year earnings to following year earnings regression coefficients. Using the samples consisting of the manufacturing companies listed at the Indonesia Stock Exchange 2016-2020, the study finds the evidence that accrual earnings management and cash flow of real earnings management negatively affect earnings persistence, while production expenditure, earnings management, discretionary expenditure, BOD size, and BOD independence positively affect earnings persistence.